2021
DOI: 10.1002/mds.28468
|View full text |Cite
|
Sign up to set email alerts
|

Brain Motor Network Changes in Parkinson's Disease: Evidence from Meta‐Analytic Modeling

Abstract: Background Motor‐related brain activity in Parkinson's disease has been investigated in a multitude of functional neuroimaging studies, which often yielded apparently conflicting results. Our previous meta‐analysis did not resolve inconsistencies regarding cortical activation differences in Parkinson's disease, which might be related to the limited number of studies that could be included. Therefore, we conducted a revised meta‐analysis including a larger number of studies. The objectives of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 88 publications
9
25
2
Order By: Relevance
“…Therefore, increased pre-SMA N40 amplitude may reflect changes along cortico-subcortical circuits in PD. 66,68 Our finding of increased pre-SMA TEPs in PD contrasts with that recently reported in a similar study. 46 However, while we centered the coil over the midline, Casarotto and colleagues stimulated a more lateral area, eliciting TEPs that may receive larger contributions from the dorsal premotor cortex (PMd).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, increased pre-SMA N40 amplitude may reflect changes along cortico-subcortical circuits in PD. 66,68 Our finding of increased pre-SMA TEPs in PD contrasts with that recently reported in a similar study. 46 However, while we centered the coil over the midline, Casarotto and colleagues stimulated a more lateral area, eliciting TEPs that may receive larger contributions from the dorsal premotor cortex (PMd).…”
Section: Discussioncontrasting
confidence: 99%
“…1,2 However, degeneration of thalamic dopamine innervation has recently been described in PD animal models, and therefore, P30 changes in PD may reflect thalamic changes unrelated to basal ganglia abnormalities. 65 Reduced M1 P30 is consistent with the reduced motor-related M1 activation reported by neuroimaging studies 66 and provides evidence of PD-related neural dysfunction that is not confounded by differences in motor task performance because TEPs were recorded at rest.…”
Section: Discussionsupporting
confidence: 80%
“…Further cross-frequency coupling (CFC) analysis revealed the abnormal CFC between the STN beta power and broadband gamma rhythm in M1. As M1 has long been implicated in the pathophysiology of PD and appeared to be one of the consistent brain areas reported in several task-based PD studies (Herz et al, 2021), it is evident that the immoderate coupling within M1 may be the representation of the cortical modification of the immoderate synchronization within the motor cortico-basal ganglia network.…”
Section: Perspectivementioning
confidence: 75%
“…3), may lead to the reduced contribution to the identifiability. To date, the quality of the alterations (in the sense of hypo/hyperactivation) related to the regions involved in the PD motor patterns is still debated 22 . With regard to the motor cortex, several studies reported controversial results when comparing PD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we obtained the time series of 116 regions of interest (ROIs), based on the AAL atlas 45 , using the volume conduction model proposed by Nolte 46 , and applying the Linearly Constrained Minimum Variance 47 beamformer algorithm included in the Fieldtrip toolbox 42 . The resulting time series were band-pass filtered in each canonical frequency band (i.e., delta (0.5 -4 Hz), theta (4 -8 Hz), alpha (8 -13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)). Only 90 ROIs were selected for further analysis, since we excluded ROIs related to the cerebellum because of low reliability.…”
Section: Source Reconstructionmentioning
confidence: 99%